But How Am I Doing? Autoethnographic Reflections of a Beginning English Language Teacher - Nycyk, Michael (Journal of NELTA, 2021)
Beginning English Language Teaching (ELT) brings many issues teachers experience that questions one’s teaching confidence and abilities. Seeking feedback from teaching peers can be invaluable, but self and student feedback can quell fears and doubts. Sharing such experiences with others involves risk, but can assist others on their journey to becoming confident ELT teachers. To reflect on my experiences as a beginning ELT teacher, an autoethnographic account is presented. It displays my fears, the need for constant feedback and the eventual acceptance that I did not need constant reassurance to evaluate my teaching performance. This account also demonstrates the usefulness and contributions that an autoethnographic account of me as a beginning teacher may bring. First, it discusses the field of beginning teaching and challenges doing ELT may bring. This is followed by an explanation of writing an autoethnography, ethical considerations and background details on this account. The autoethnographic account is written using constructed vignettes to demonstrate moments of crisis and resolution. This account closes with a discussion and some conclusions about the value of using autoethnography in the ELT field.